PERBEDAAN PENYESUAIAN SOSIAL PADA ANAK YANG MENJALANI SISTEM PEMBELAJARAN TAMAN KANAK-KANAK FULL DAYS DAN REGULER - Yuninta Ayu Brianti; Suci Murti Karini; Rin Widya Agustin (Wacana, 2010)
Kindergarten full days is a full days learning concept, which educates children in the school environment from morning till evening. Unlike regular kindergarten which organizes activities until 10:00. The phenomenon of the learning system has an effect also produce different abilities including social adjustment. Social adjustment was instrumental in the development of children so that they can establish good relationships with others. Both these learning systems have made possible a different effect in child development including social adjustment. This study aimed to find out the difference of social adjustment in children who undergo a learning system kindergarten full days and regular. This study uses the entire population as a sample because the number of kindergarten children in KB TKI Mulia Hati Klaten and TK Aisyiyah Bustanul Athfal Kalikotes 1 Klaten too little, so this research is the study population. This study uses a quantitative approach with cross sectional method. Data collection tool used is the scale of social adjustment. Data analysis using analytical techniques independent sample t-test. Categorization results showed that the general subject in the learning system a full kindergarten days and regular has a high level of social adjustment, but there are differences in the mean 1.30 which shows the differences in social adjustment in children who undergo the learning system is a full kindergarten days and regular, although the differences were less learning system can be used as a predictor of social adjustment. It was not statistically significant due to test independent sample t-test resulted t-count = 0.934 and t-table = 1.980, with probability p-value = 0.352 > α = 0.005. This means that the hypothesis is rejected, there is no difference of social adjustment in children who undergo a learning system kindergarten full days and regular. Results of data analysis to produce an average value of regular kindergarten 78.38 and kindergarten full days 77.08. This means that learning the system a regular kindergarten have higher social adjustment rather than a kindergarten full days.     Keywords: social adjustment, kindergarten full days, the regular kindergarten